Optimization of modified-media containing serum for better rin-5f and brin-bd11 cells monolayer attachment, growth and insulin secretion - Abdul Karim, Mohamed Ismail (2009)
A study was undertaken to observe the effect of D-glucose and L-glutamine and the combination of both nutrients at various concentrations towards the growth and insulin production by BRIN-BD11 cells. It was found that at a final concentration of 4 g/L D-glucose and 0.3 g/L L-glutamine in RPMI-1640 media gave maximum cell growth and insulin production of 1.75 x 106 cells/ml from 2.5 x 105 cells/ml and 100.77 µg/L, respectively. The result of this study indicates that D-glucose and L-glutamine promote good cell growth and insulin secretion of BRIN-BD11 cells as a step towards mass propagation of transplantable insulinoma cells and insulin production.